Sauna, the Cardiovascular System and Autonomic Regulation: Implications for Post-exercise Recovery : – A Narrative Review of the Literature - Karol, Michał; Koseska, Kamila; Borowicz, Jan; Górecki, Bartosz; Kloch, Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Strawińska, Aleksandra; Bednarczyk, Małgorzata (Quality in Sport, 2026)
Introduction: Sauna bathing, traditionally associated with relaxation in Nordic countries, is increasingly regarded as a tool supporting cardiovascular prevention and post-exercise recovery. As its use becomes more widespread, questions arise about the safety of this form of heat exposure, the mechanisms by which it affects the cardiovascular system and autonomic regulation, and how it can be integrated into training programmes for athletes and physically active individuals. Aim: The aim of this narrative review is to organize current knowledge on the acute and chronic effects of sauna bathing on haemodynamic parameters, sympathetic–parasympathetic balance and post-exercise recovery, with particular emphasis on potential benefits, risks, contraindications and practical aspects of dosing the thermal stimulus. State of knowledge: Available studies indicate that a single sauna session induces predictable circulatory changes – peripheral vasodilation, an increase in heart rate and cardiac output with a moderate reduction in arterial blood pressure, and transient hypovolaemia. Regular sauna bathing has been associated in long-term observations with a more favourable cardiovascular profile, improvement in selected indices of sinus rhythm variability, better subjective well-being and improved exercise tolerance. In athletic populations, sauna may support the perception of recovery, promote muscle relaxation and facilitate glycogen resynthesis, provided that it is used with adequate attention to hydration and appropriate dosing of heat stress. Conclusions: Sauna appears to be a valuable and relatively simple adjunct to cardiovascular prevention strategies and recovery programmes, but it does not replace physical activity or causal treatment. Further interventional studies are needed to refine optimal protocols of sauna bathing in the general population and in elite sport, and to better define groups in whom the benefits outweigh the risks.